Annual Plan 2006-07 Government of Bihar - Planning Commission (Planning Commission, 2006)
The State of Bihar was reorganized on 15th November, 2000 with 38 districts of erstwhile undivided Bihar. the reorganized State has an area of 94,163 sq.km, and a population of 82.998 million according to the 2001 Census. the population of the State constitutes 8.07 percent of the country with about 3 percent of the area thereof. The adverse land-man ratio is reflected in the high density of population, which is 880 per sq.km. the decadal growth of population for 1991-2001 has been 28.43% which is highest in the country. the literacy rate in the state is 47.58% according to 2001 census a against 38.50% in 1991.
Planning and Development Department Government of Bihar